2016
DOI: 10.1007/s00384-016-2663-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response to gluten-free diet as evidence for non-celiac wheat sensitivity in one third of patients with diarrhea-dominant and mixed-type irritable bowel syndrome

Abstract: PurposeIrritable bowel syndrome (IBS) is common but therapies are unsatisfactory. Food is often suspected as cause by patients, but diagnostic procedures, apart from allergy testing, are limited. Based on the hypothesis of non-celiac wheat sensitivity (WS) in a subgroup of IBS patients, we tested the long-term response to a gluten-free diet (GFD) and investigated HLA-DQ2 or -DQ8 expression as a diagnostic marker for WS in diarrhea-dominant (IBS-D) and mixed-type IBS (IBS-M).MethodsThe response to a GFD served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 43 publications
2
46
0
4
Order By: Relevance
“…Non‐randomized clinical trials: Two studies have shown improved symptoms following 4‐6 month use of the gluten‐free diet in IBS …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…Non‐randomized clinical trials: Two studies have shown improved symptoms following 4‐6 month use of the gluten‐free diet in IBS …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
“…Trials assessing effect by genotype: One RCT showed greatest effect in HLA‐DQ2/8‐positive patients; another showed improvement in 60% of HLA‐DQ2‐positive patients and only 12% who were HLA‐DQ2‐negative . While another study showed no association between genotyping and response …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Because studies have shown that a gluten-free diet can improve IBS symptoms, at least in some patients, nonceliac wheat sensitivity may comprise a subset of patients with IBS [40,42]. A gluten-free diet was also shown to improve IBS-related QOL from baseline in some patients with IBS [43]. This may partly be related to GI mucosal changes observed in patients with IBS with a suspected food intolerance; these changes include epithelial barrier disruptions, fluid secretion into the GI lumen, and an influx of intraepithelial lymphocytes [44].…”
Section: Gluten-free Dietsmentioning
confidence: 99%